Repopulating and revitalising rural Sweden? Re‐examining immigration as a solution to rural decline. Issue 4 (31st August 2017) - Hedlund, Martin; Carson, Doris A; Eimermann, Marco; Lundmark, Linda
Abstract : Increasing international immigration is often portrayed as a potential solution to persistent economic and population decline in rural areas. Based on longitudinal register data, this study examines the extent to which international migration has contributed to demographic and labour market changes in rural Sweden between 1990 and 2010. Results show that the urbanisation rate of international migrants is very high while their employment rate in rural areas remains comparatively low. Small positive changes are noticeable in the rate of higher education, self‐employment and employment in new service‐related industries among particular groups of immigrants. Immigrants to rural areas are a highly heterogeneous group in terms of their demographic and labour market characteristics, which should be considered when estimating the contributions of immigration to socio‐economic development in rural areas. This study shows that, while international migration may dampen population decline in rural areas to some extent, particularly in the working‐age groups, its potential to stimulate socio‐economic revitalisation in rural areas needs to be questioned and examined from a more nuanced and longitudinal perspective.